Clinical implications of photophobia in progressive supranuclear palsy. (2021) - Mohanty, Deepankar; Hay, Kaitlyn R.; Berkowitz, Sean; Patel, Shriji; Lin, Ya-Chen; Kang, Hakmook; Claassen, Daniel O.
Highlights: Photophobia is a common, disabling symptom observed in patients with Progressive Supranuclear Palsy (PSP). We assessed the functional impacts of photophobia in PSP, and find that bright light is painful. Symptoms limit participation in activities of daily living, reducing time spent outside the house. Abstract: Objective: To determine the impact of photophobia on persons with Progressive Supranuclear Palsy (pwPSP) by determining the functional impact of light sensitivity using methods established in migraine research. Methods: All 60 participants (pwPSP = 15, persons with Parkinson Disease (pwPD) = 15, Older adults = 30) completed a series of questionnaires designed to assess the impact of photophobia on activities of daily living. Group comparisons were controlled for multiple comparisons using a false discovery rate of 0.05. Results: Most (14/15) pwPSP participants noted that bright light hurt their eyes, and this proportion was significantly greater than pwPD (6/15; p = 0.03, corrected). PSP participants reported statistically significantly more severe light sensitivity on a subjective 0–100 scale (p = 0.003, corrected), and noted reduced time spent in both indoor and outdoor activities. Some PSP participants (n = 3) noted that they needed to wear sunglasses indoors, but most noted a reluctance to leave their house during the day due to photophobia. PwPSP indicated that they require more help from others to complete daily tasks that require them to be outside during daylight hours. Conclusions: Overall, we note a significant debility due to photophobia in PSP, and this impacts outdoor more than indoor activities. The functional disability in PSP caused by photophobia appears to cause a substantive reduction in quality of life. Future studies could consider incorporating specific metrics to evaluate measurable differences with photophobia onset and worsening severity.